Connecting Civics to Life Around Us: An Experiment with Municipal Corporation Schools in Pune Region, India A Qualitative Study - Bhave, Bhakti; Suhas, Kaamini Jayashree; Barve, Apurva (JOURNAL OF INDIAN EDUCATION, 2019)
Informed, active and responsible citizenry is fundamental for democracy to sustain and flourish. Research suggests that the impetus civic awareness and responsibility start at adolescent age. Hence, it is important that schools use methodologies that make civic education interesting, practical and relevant. Current study explores an educational intervention called Civic Action Project (CAP). The study adopted quasi experimental research design. The experimental group students underwent CAP intervention, whereas the control group students did not undergo CAP and received regular teaching. Purpose of the study was to investigate how students put their knowledge and skills to use while responding to solve a hypothetical civic issue (using a vignette). Further, the study aimed to examine dispositions reflected in their responses. Qualitative methods were used for data collection and analyses. Findings of the study show that hands on experience in interventions like CAP can help teachers encourage competent civic engagement among students.